Nginx From Beginner to Pro - Soni, Rahul (Apress : Imprint: Apress, 2016)
This book teaches you to start up Nginx and quickly take your expertise to a level where you can comfortably work with various aspects of the web server and make informed design decisions for your web farm. Nginx powers more than 40% of the top 1000 websites and is among the handful of web servers that can handle more than 10K simultaneous connections. It has some features which are simply unparalleled. Nginx: From Beginner to Pro teaches the Nginx server in a practical way. Web administrators frequently struggle to fix the skill set gaps that happen due to a platform change. Migration from IIS & Apache becomes tedious at best. The book is targeted toward real-world administrators who would want to get up to speed as soon as possible and make good, informed design decisions. First you will set up Nginx and understand the architectural nuances. Then you will learn how to scale out, secure, monitor and troubleshoot the web server. Once you are fully comfortable with Nginx, you will start learning about migrating applications (or its part) from IIS or Apache web servers. Finally, you will learn to troubleshoot and maintain your Nginx professionally. Written by an author who has gone through the rough phase while moving from IIS/Apache to Nginx, this book is practical and filled with step-by-step instructions to make your time with Nginx as straightforward as possible. .